Emerging Insights on Caspases in COVID-19 Pathogenesis, Sequelae, and Directed Therapies - Premeaux, Thomas A.; Yeung, Stephen T.; Bukhari, Zaheer; Bowler, Scott; Alpan, Oral; Gupta, Raavi; Ndhlovu, Lishomwa C. (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), remains a significant global health emergency with new viariants in some cases evading current therapies and approved vaccines. COVID-19 presents with a broad spectrum of acute and long-term manifestations. Severe COVID-19 is characterized by dysregulated cytokine release profile, dysfunctional immune responses, and hypercoagulation with a high risk of progression to multi-organ failure and death. Unraveling the fundamental immunological processes underlying the clinical manifestations of COVID-19 is vital for the identification and design of more effective therapeutic interventions for individuals at the highest risk of severe outcomes. Caspases are expressed in both immune and non-immune cells and mediate inflammation and cell death, including apoptosis and pyroptosis. Here we review accumulating evidence defining the importance of the expression and activity of caspase family members following SARS-CoV-2 infection and disease. Research suggests SARS-CoV-2 infection is linked to the function of multiple caspases, both mechanistically in vitro as well as in observational studies of individuals with severe COVID-19, which may further the impact on disease severity. We also highlight immunological mechanisms that occur in severe COVID-19 pathology upstream and downstream of activated caspase pathways, including innate recognition receptor signaling, inflammasomes, and other multiprotein complex assembly, inflammatory mediators IL-1β and IL-18, and apoptotic and pyroptotic cell death. Finally, we illuminate discriminate and indiscriminate caspase inhibitors that have been identified for clinical use that could emerge as potential therapeutic interventions that may benefit clinical efforts to prevent or ameliorate severe COVID-19.